Brain Activity For Long-term Memory During Retention and Recalling Process In Learning Using Multimedia - HANOUNEH, SAMER (2016)
Including multimedia as a part of instruction can significantly enhance student learning. Therefore, understanding the effects of using multimedia on brain activities during memory recall can help to build better learning system which reflects increasing in memory performance for the learners. Few interesting previous studies investigated the effects of using multimedia subjectively as well as objectively but for short-term memory only, while long-term memory previous studies used only subjective measurement. Thus, this research focuses in investigating the effects of using multimedia on long-term memory using subjective feedback and EEG signals for objective measurement. Electroencephalogram (EEG) is an important neuroimaging modality which allows studying the changes in brain neuronal networks related to cognitive processes. In this study, we investigated the relationships between EEG and long-term memory recall process using spectral analysis, and functional connectivity. An EEG dataset was employed from previous study, which was recorded during memory recall process from 34 healthy participants. The dataset consists of two tasks, (i) learning task, to study the animated learning material and (ii) memory recall task for recording the behaviour responses during memory process as well as assessment of neuronal networks. EEG signals recorded during memory recall task along with behaviour responses were analysed in this study. Spectral analysis such as absolute power and relative power of EEG frequency bands results showed EEG regional delta, theta and high-beta and inter-regional alpha and gamma activity correlate with memory performance which reflects mental activity and representation process.